2008
DOI: 10.1007/s11252-008-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Green roofs are not created equal: the hydrologic and thermal performance of six different extensive green roofs and reflective and non-reflective roofs in a sub-tropical climate

Abstract: Green roofs have the potential to retain stormwater on the roof surface and lower the thermal loading on buildings. Because of this, the greatest environmental benefits from green roofs might be achieved in subtropical climates characterized by high temperatures and intense rain events. There is, however, little research to support this. In a replicated study in Texas, we compared the performance of six different extensive green roof designs vegetated with native species, to non-reflective (black) roofs, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(131 citation statements)
references
References 11 publications
8
95
0
5
Order By: Relevance
“…Carter and Rasmussen [12], in Georgia, have shown that, for small rainfall events (<25.4 mm), the 88% of the stormwater volume was retained, for an average rainfall (25.4-76.2 mm) more than the 54%, and for the events higher than 76.2 mm, 48%. Similarly, Simmons et al [23], in Texas, have demonstrated that, while small rainfall events (<10 mm) were totally retained by the green roof, rainfall events with a total depth of 49 mm and a duration of 140 min produced a retention efficiency up to 44%. Villareal and Bengtsson [25] (in Lund) have observed that the retention of a green roof largely depends on the intensity of rainfall; in fact, lower rain intensity events produce greater retention.…”
Section: Factors Influencing the Hydrological-hydraulic Behavior Of Amentioning
confidence: 75%
See 2 more Smart Citations
“…Carter and Rasmussen [12], in Georgia, have shown that, for small rainfall events (<25.4 mm), the 88% of the stormwater volume was retained, for an average rainfall (25.4-76.2 mm) more than the 54%, and for the events higher than 76.2 mm, 48%. Similarly, Simmons et al [23], in Texas, have demonstrated that, while small rainfall events (<10 mm) were totally retained by the green roof, rainfall events with a total depth of 49 mm and a duration of 140 min produced a retention efficiency up to 44%. Villareal and Bengtsson [25] (in Lund) have observed that the retention of a green roof largely depends on the intensity of rainfall; in fact, lower rain intensity events produce greater retention.…”
Section: Factors Influencing the Hydrological-hydraulic Behavior Of Amentioning
confidence: 75%
“…Locatelli et al [20] have noted that the delay of the peak flow rate was up to 40 min, while Getter et al [10] and Villarreal and Bengtsson [25] have found minimal delays. However, for the majority of studies the delay of the peak flow rate was found to be up to 30 min [12,23].…”
Section: Factors Influencing the Hydrological-hydraulic Behavior Of Amentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to reflective roofs, green roofs have better performances in cold climates and in non-insulated buildings [158,159]. Under certain conditions, green roofs are more effective in reducing surface temperature [52], indoor air temperature [160], and annual building energy loads [161]. Even in terms of pavements, albedo is not the only determinant parameter that affects the thermal performances.…”
Section: Discussionmentioning
confidence: 99%
“…Bu sayede şiddetli yağmurlarda yeşil çatılara gelen yağmur suları tutulur ve belli bir süre sonra şebekeye gönderilir. Böylelikle şebekelerdeki yağmur yükü hafiflemekte, debi pikleri düşmekte ve taşkın riski azalmaktadır [17][18].…”
Section: ġEkil 1 Yeşil Teras çAtıunclassified